TOPOLOGY OPTIMIZATION OF COUPLER IN LIGHT RAIL TRANSIT WITH GRADIENT BASED METHOD - Nur Badruddin, Muhammad
The development of mass transportation is being increase because of the high growth of population in Indonesia. One of the mass transportations that be used is Light Rail Transit or LRT. To save the energy that consumed by the LRT the design must be the optimum. The criteria to obtain optimum design, the structure mush be lightweight and strong enough. One of component in LRT is coupler, the connector of each carbody. In Indonesia AAR type coupler is used in all type of train including LRT, although this type of coupler should be installed in conventional train that has more weight and load. In this research, a numerical simulation being conducted using software Altair Hyperworks Optistruct to redesign the coupler of LRT. The method of the optimization is by iterating the design to get most optimum design called gradient based method. This research also conducted modular design to be implemented to the design in LRT. In early design, the CAD model is made based on technical drawing from PT Barata Indonesia to get the analysis of the strength of the structure. The optimization started by varying the variable that can be affect the result of optimization. The final design after optimization is obtained by reduction of 27% in weight and the structure still strong enough to loaded by compression load and tension load. The structure meets the requirement to not permanently deformed and not buckle.